Perancangan Sistem Pemenuhan Material Minibus PT XYZ dengan Metode System Development Life Cycle - Samudra, Eko Roby; Hadi, Yuswono; Oktiarso, Teguh (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2023)
The welding department is the focus of this study. This department welds and assembles various materials from the warehouse and supporting departments into complete minibuses. Several issues exist, such as material delivery delays occurring 1-3 times per production process, material delivery errors, increased production lead time from 12-13 working days to 15-16 working days, and the lack of a clear SOP for material fulfillment. To address these issues, a material fulfillment system design is necessary, utilizing the System Development Life Cycle (SDLC) analysis. The SDLC analysis suggests that solutions include grouping materials into kitting packages, developing system programs, improving system flow, and creating an SOP. These solutions can be directly implemented in the welding department's production process at PT XYZ. The implementation results show that materials needed by the welding department can be divided into seven kitting packages according to existing workstations. The new system flow reduces material delivery delays to less than one working hour, aligns production lead time with the company's target of 12-13 working days, reduces material delivery errors, and the implemented SOP aids all parties in the minibus production process. These measures must be consistently monitored to avoid disrupting the production process and to meet the company's production lead time targets.